COVID-19 in Pediatric Patients: A Focus on CHD Patients - Zareef, Rana O.; Younis, Nour K.; Bitar, Fadi; Eid, Ali H.; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2020)
Coronavirus disease 2019 (COVID-19) is a global pandemic caused by SARS-CoV-2 virus. As of the 30th of September 2020, around 34,000,000 cases have been reported globally. Pediatrics with underlying congenital heart disease represent a small yet a critical proportion of these patients. In general, the majority of infected children experience mild to moderate disease with significant interindividual variability in laboratory and radiographic findings. Nevertheless, in healthy children with COVID-19, cardiac involvement has been documented and is attributed to various causes. Myocarditis, arrhythmias, cardiogenic shock and serious multisystem inflammatory syndrome in children are all encountered. Since COVID-19 is a recent novel disease and based on previous experience with respiratory infections, children with underlying congenital heart disease should be given special attention. To date, little data is available about COVID-19 presentation, complications, and appropriate treatment in this population. However, variable and inconsistent disease presentation and severity have been observed. This paper discusses COVID-19 course of illness in pediatric population with a special emphasis on the cardiac manifestations of the disease in healthy population and also on the disease course in congenital heart disease patients in particular.